Internal marketing - Çiçekdağ, İdil (My University, 2000)
Bu tezin yazarı firma içi pazarlama stratejisinin gerekliliği, yaratılması, ve başarılı uygulaması için atılması gereken adımları irdelemiştir. Firma içi pazarlama yaklaşımı şirket personelinin şirket için hedef pazar olduğunu ileri sürmektedir. Firma içi pazarlama fonksiyonunun amacı motive olmuş ve müşteri odaklı çalışanlar elde etmektir. Örneğin personel yönetimi, organizasyonel teori, üretim planlama gibi alanlarda firma içi pazarlama devreye girmektedir. Çalışanların motivasyonunun sağlanmasındaki nihai amaç iç ve dış müşteri memnuniyetinin sağlanmasıdır. Firma içi pazarlamanın şirketin müşteri ile ilişkisi olan çalışanlarını müşteri memnuniyetinin sağlanması amacıyla takım çalışmasına yöneltilmesidir. Takım çalışmasına yöneltirken de eğitim ve motivasyone önem verilmesi gerekmektedir. Firma içi pazarlamanın odak noktası hem iç hem de dış müşteriye serviste en iyi şekilde hazırlanmak için gerekli motivasyonun ve eğitimin sağlanmasıdır. Bu araştırmada 12 şirketten 250 adet anket toplanmıştır. Araştırmanın yapılmasındaki amaç firma içi pazarlamanın dış müşteri memnuniyetini arttırmada iç müşteri motivasyonunun önemli olduğunun kanıtlanmasıdır. EXECUTIVE

The author of this thesis has investigated the necessity of an internal marketing strategy and the prerequisites for the successful implementation and has presented the specific steps in developing and implementing an internal marketing approach. EXECUTIVE SUMMARY The author of this thesis has investigated the necessity of an internal marketing strategy and the prerequisites for the successful implementation and has presented the specific steps in developing and implementing an internal marketing approach. The internal marketing approach puts forward that company personnel is the first target market of a service company. The objective of an internal marketing function is to obtain motivated customer focused personnel. Motivation is by no means a new concept in the business context. For example, in the personnel administration, organisational theory and production planning fields, internal marketing has been introduced in order to motivate employees. The ultimate reason for motivating employees should be internal and external customer satisfaction. Internal marketing describes the work done by the company to train and motivate its internal customers, namely its customer contact employees and supporting service personnel to work as a team to provide customer satisfaction(Kotler P. Marketing Management Analysis, Planning, Implementation and Control, 1991) Internal Marketing focuses on ensuring that employees are well trained and motivated in preparation to serve both internal and external customers; employees understand the business in its entirely with its mission and practices
Keywords: Genel yönetim; Pazarlama yönetimi; PAZARLAMA-STRATEJİLER